THE INFLUENCE MUSIC AND MOVEMENT METHOD TO INTRODUCTION ENGLISH IN THE KINDERGARTEN ISLAM DAUD KHALIFATULLOH PADANG - Aisah, Romai (journal of residu, 2019)
Music and movement method is one method of recognizing English in children through movement and song. The implementation of this study with the aim of knowing the influence of the music and movement method has an effect on the introduction of children's English in the Islam Daud Khalifatulloh Padang Kindergarten. The research method is a quantitative method with experimental quasy types. The test is used as a data collection technique, in the form of a statement of 9 items, then the data is processed using a different test (t-test). The results of the data analysis of the experimental group obtained an average using the music and movement method 79.25 and 72.03 the control group with image media. These results can be concluded that the music and movement method influences the introduction of children's English in the Islam Daud  Khalifatulloh Padang Kindergarten